PELATIHANPUBLIC SPEAKINGPADA REMAJADAN ANAK-ANAKDUSUNPULUHAN, DESA BANYUSIDI, PAKIS, MAGELANG,JAWA TENGAH - Muhammad Hasyim (Asian Journal of Innovation and Entrepreneurship, 2014)
Public speaking is a skill that is more special than just talking to other people.Public speaking requires more preparation than just talk because it is aimed atcommunicating about a topic in front of many people to influence, persuade, changeopinions and to provide information. Hence the holding of a workshop on publicspeaking to children and  teenagers Puluhan village to inforem them the importance ofhaving public speaking skills and improvethese skills. Especially when they have enteredthe public will be much needed in the future, the education about public speaking needto know early on.